Profilaxis oftálmica como recomendación para la práctica durante el periodo de transición en el recién nacido (2022)
Ophthalmia neonatorum is characterized by the presentation of conjunctivitis in the infant during the first month of life, it can be caused by an infection with Neisseria gonorrhoeae (N. gonorrhoeae), Chlamydia Trachomatis (C. trachomatis) or other bacteria or virus (1). As a result, since 1880 preventive health interventions began to be implemented by health professionals in the transitional period of the newborn, and prenatal therapeutic management has been implemented to avoid the infection and clinical presentation of neonatal ophthalmia. The objective of this review is to strengthen the recommendations postulated in the newborn care CPG based on scientific evidence. Methodological design: Bibliographic review with the application of the five phases of Evidence-Based Nursing in the Cochrane library, Pubmed and Scopus databases. Results: We consolidated 21 interventions at a general level that have emerged over time. Silver nitrate 1% is related to present chemical conjunctivitis in 50-90%, Erythromycin 0.5% is more effective and is recommended by the FDA, Povidone Iodine 1.25